Colonic Pseudo-obstruction as a Rare Complication of Pheochromocytoma - Kin Wai So; Hoi Ling Tsui; Kim Hung Tsang (European Journal of Case Reports in Internal Medicine, 2021)
Colonic pseudo-obstruction is characterized by dilatation of the colon without a structural lesion causing the obstruction. It usually involves the caecum and right side of the colon and is commonly observed in patients with severe illness or after surgery; it is rarely caused by pheochromocytoma. The diagnosis of colonic pseudo-obstruction can be established by abdominal imaging including computed tomography (CT) of the abdomen or use of a water-soluble contrast enema. In additional to conservative or surgical treatment, alpha-blockers can be used in this setting to relieve the pseudo-obstruction.